Fintech development in Hong Kong, China - Yvonne Tsui; Hongyi Chen; Chris Ip; Bernia Lee (Asian Development Bank Institute (ADBI), 2019)
Major fintech advancements in recent years have attracted the attention of financial regulators around the world, including the Hong Kong Monetary Authority (HKMA). HKMA stands ready to embrace technology and innovations that emerge in the course of fintech development. In particular, HKMA adopts a risk-based and technology-neutral approach in its supervision. To achieve that, HKMA emphasizes three key factors: its willingness to learn about and understand fintech; its ability to maintain close contact with the industry and other stakeholders; and its ability to achieve a good balance between market development and customer protection. HKMA also maintains close contact with the industry and regulators in other jurisdictions to ensure the existing regulations are up to date. The most recent fintech developments spearheaded by HKMA include: (1) open application programming interface for banks; (2) faster payment system (FPS) and common QR code standard for retail payments; (3) trade finance initiatives; and (4) virtual banking. HKMA has devoted substantial resources to research and application. Some of the research output has already been adopted and is being used by the industry.
Keywords: B27; G23; O16; P33; P45; 330; fintech; trade finance initiatives; virtual banking; Hong Kong; China